Influence of a pre-existing basement weakness on normal fault growth during oblique extension: Insights from discrete element modeling. (December 2017) - Deng, Chao; Gawthorpe, Robert L.; Finch, Emma; Fossen, Haakon
Abstract: We use discrete element modeling to investigate three-dimensional fault geometry and the three-dimensional evolution of a fault network that develops above a 60° dipping planar pre-existing weakness striking 60° relative to the extension direction. The evolution of the fault network comprises three stages: (i) reactivation of pre-existing structure and nucleation of new faults (0–10% extension); (ii) radial propagation and interaction between reactivated structure and new faults (15%–20% extension); and (iii) linkage between reactivated structure and adjacent faults (20%–25% extension). During the first stage, the pre-existing structure mostly reactivates, forming a long and under-displaced fault. New faults are mainly extension-perpendicular and dip at 60°. During the second stage, 'saw-tooth' fringes grow upwards from the upper tip of the reactivated structure (which becomes the major fault) and influence the density and orientation of surrounding faults. During the third stage, the reactivated structure links laterally and vertically with adjacent faults, creating non-planar fault geometries. Following linkage, the reactivated structure enhances the displacement of linked faults along branch lines. Our study demonstrates that pre-existing weak faults can be reactivated, propagating upwards in an irregular ('saw-tooth') pattern, and affecting fault density, orientation, dip and displacement, and providing the nucleation site of new faults. Highlights: Reactivation and growth of a basement structure during rifting in three dimensions. Upward propagation of a reactivated structure via 'saw-tooth' fringes. Influence of a basement structure on new fault growth in three dimensions. Formation of non-planar faults owing to influence of a basement structure.